now apply the initial condition...
So I've attempted this problem sooo many times! And I don't know where I'm going wrong. I've also consulted many friends in my class and they're also stuck. So here it goes....
du/dt = e^(2.6t-3.1u), u(0)= 1.9
So what I did was:
du/dt = e^(2.6t)/e^(3.1u)
e^(3.1u) du = e^(2.6t) dt
INTEGRATE BOTH SIDES
1/3.1 (e^3.1u) = 1/2.6 (e^2.6t) + C
and then I solved for C:
C= (1/3.1)e^(5.89) - (1/2.6)
and then my u(t) equation was:
[(2.6t(ln(1/2.6)) + 5.89(ln(1/3.1)) - ln (1/2.6))/(ln(1/3.1))]/(3.1)
which is wrong.
so if anyone can help out that would be great!!